PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GRU MIPA SMP KABUPATEN MAMBRAMO TENGAH - PAEMBANG, PERTY MINCE; SIREGAR, TIURLINA (Jurnal Ilmu Pendidikan Indonesia, 2018)
Abstract Research has been carried out of the title â€œHeadmaster leadership, the work motivation and the work discipline for the work result by MIPA teacher of Junior High School in Mamberamo Tengah Regencyâ€. This research aims for test and analyze the influence the principal leadership, work motivation and work discipline for the work result by MIPA teacher of Junior High School in Mamberamo Tengah regency. Method used in this study is descriptive analysis methods, the data collection was conducted through quessionaires and implemented for 15 people (5 Headmasters of Junior High School and 10 Teachers of MIPA og Junior High School) in Mamberamo Tengah Regency. Data analysis in this study using the helpof SPSS version 16. Sampling technique was used and the method of testing techniques census data that in used in this study include test validity and rehabilitation, the classic assumption test and multiple linearregression analysis. The analyze result of Headmasterâ€™s leadership of data preparation result included very goog category. The statistic calculation result indicate that value of t arithmetic = 3,045 with using significant limit 0,001 more trivial than 0,05, it means that the Headmaterâ€™s leadership has influence for the MIPA teahcer in Junior High School in Mamberamo Tengah regency. The work motivation that included intrinsic and extrinsic motivation approriate with data preparation result included good category. The statistic calculation result indicate that value of t arithmetic = 1,358 with using significant limit 0,202 more big than 0,05, it means that the work motivation doesnâ€™t has influence for the MIPA teacher of Junior High School in Mamberamo Tengah regency. The work discipline that include accuracy of time, the realization in work and discipline for the result approriate with the result of data preparation include good category. The statistic calcultion result indicate that value of t arithmetic = 2,578 with using significant limit 0,026 more trivial than 0,05, it means that work discipline has influence for the work result of MIPA teacher of Junior High School in Mamberamo Tengah regency. The work result of MIPA teacher of Junior High School in Mamberamo Tengah regency that include educate, teach, lead to aim, train, appraise and evaluate appropriate with the data preparation include good cateogry. The statistic calculation result indicate that value of t arithmetic = 10,187, with using significant limit 0,002 more trivial than 1,05. According to variable simultaneous the leadership of headmaster, work motivation and work discpline have influence for the teacherâ€™s work result. Keywords : Leadership, Motivation, Work Discipline, Teacherâ€™s Work Result